Capture of CO2 by vermiculite impregnated with CaO - Matheus Henrique Simplício Pereira; Cláudio Gouvêa dos Santos; Geraldo Magela de Lima; Carlos Giovani Oliveira Bruziquesi; Victor de Alvarenga Oliveira (Carbon Management, 2022)
Vermiculite samples were impregnated with different amounts of calcium oxide by the conventional thermal heating technique and subject to CO2 capture experiments in thermal analysis equipment. The amount of CO2 captured by calcium oxide increased from 13 g of CO2 per mol of CaO to 16.8 g of CO2 per mol of CaO when the experiments were carried out with pure calcium oxide and vermiculite impregnated with CaO (1:1), respectively. Integral isoconversional methods of Kissinger-Akahira-Sunose (KAS) and Osawa-Flynn-Wall (OFW) were used for the kinetic study of the process and good correlation coefficients were achieved. The apparent activation energy values showed that for low conversions (α < 0.3) the controlling step of the process is a mixed step where the chemical reaction and the diffusion of the reagents into the vermiculite have rates of the same order of magnitude (20 kJ < Ea < 40 kJ). For higher conversions values (α > 0.3) the apparent activation energy values suggest that the slow step is a chemical step (Ea> 40 kJ).